High-Throughput Sequencing-Based Analysis of T Cell Repertoire in Lupus Nephritis - Ye, Xiaolan; Wang, Zhe; Ye, Qiang; Zhang, Jing; Huang, Ping; Song, Jingying; Li, Yiwen; Zhang, Hongjuan; Song, Feifeng; Xuan, Zixue; Wang, Kejian (Frontiers in Immunology, 2020)
T cell receptor (TCR) mediated immune functions are closely related to autoimmune diseases, such as systemic lupus erythematosus (SLE). However, technical challenges used to limit the accurate profiling of TCR diversity in SLE, and the characteristics of SLE patients remain largely unknown. In this study, we collected peripheral blood samples from 10 SLE patients with lupus nephritis (LN) who were confirmed by renal biopsy, as well as 10 healthy controls. The TCR repertoire of each sample was assessed by high-throughput sequencing to examine the distinction between SLE subjects and healthy controls. Our results showed statistically significant differences in TCR diversity and usage of TRBV/TRBJ genes between the two groups. A set of signature V-J combinations enabled efficient identification of SLE cases, yielding an area under the curve (AUC) of 0.89 (95% CI: 0.74-1.00). Taken together, our results revealed the potential correlation between the TCR repertoire and SLE status, which may facilitate the development of novel immune biomarkers.